The chaperone [videorecording (DVD)] - Richardson, Haley Lu; Otto, Miranda; McGovern, Elizabeth, 1961- (PBS, 2019)
Society matron Norma Carlisle volunteers to accompany future Jazz Age star and free spirit Louise Brooks for a summer in New York. But why does she want to go? It's a story full of surprises, about who these women really are, and who they eventually become. Written by Julian Fellowes and based on the beloved novel by Laura Moriarty.